Unravelling poly(1-vinyl-1,2,4-triazole) hydrogels behaviors and enhancing 5-Fluorouracil delivery systems by utilizing a fuzzy modelling approach - Bayramgil, Nursel Pekel; Insel, Mert Akin; Kocken, Hale Gonce; Albayrak, Inci; Karakus, Selcan (IOP Publishing Ltd, 2024)
In recent years, fuzzy-hybrid systems have been reported in biomedical applications due to their ability to handle uncertainties, provide flexibility, identify optimal production processes, and integrate experimental data sources to create reliable decision support mechanisms. This study focuses on introducing a fuzzy-hybrid methodology to model the swelling behavior of poly(1-vinyl-1,2,4-triazole) (PVTAz) hydrogels and the drug release profile of PVTAz hydrogels loaded with 5-Fluorouracil. The proposed fuzzy-hybrid approach was utilized in modelling swelling behavior of the PVTAz hydrogels as a fuzzy function of time, temperature, pH, and the drug release behavior as a fuzzy function of time only. All the obtained models were illustrated with respect to the experimental data, showing their effectiveness and applicability. Performance metrics (ARE, RMSE, R2) were calculated for the fuzzy-hybrid supported swelling behavior and drug release models: (ARE = 6.9492, RMSE = 150.59, R2 = 0.9529) and (ARE = 4.2956, RMSE = 2.2889, R2 = 0.9879), respectively. This study significantly advances our understanding of hydrogel behaviors in drug delivery systems, highlighting interdisciplinary synergy that enhances research outcomes.
Keywords: fuzzy regression; mathematical modelling; 5-Fluorouracil; swelling behavior; drug release behavior; LINEAR-REGRESSION ANALYSIS; DRUG-RELEASE; HYBRID; Physics